Diagnostic and therapeutic approaches for enhancing reproductive efficiency in female dogs - Deepthi L (Department of Animal Reproduction, Gynaecology and Obstetrics, College of Veterinary and Animal Sciences, 2010)
The present study was undertaken for finding optimal breeding time in bitches, early pregnancy diagnosis and tackling pseudopregnancy using antiprolactin drugs. Experiment consisted of 55 apparently healthy bitches which were brought to the Small Animal Obstetrics and Gynaecology unit of Veterinary College Hospital, Mannuthy and University Veterinary Hospital, Kokkalai for getting breeding advice. Fertility rate was assessed in two different groups viz., Group I (n=30) and Group II (n=25). The conception rate was 73.3 per cent in group I and 88.0 per cent in group II. Conception rate was more in those animals, which were bred, based on vaginoscopy than those bred based upon clinico-gynaecological examination and vaginal exfoliative cytology. This supported the view that performing vaginoscopy will augment conception rate in bitches. Clinico-gynaecological examination together with vaginal exfoliative cytology was found to be useful for finding optimal breeding time in bitches under field conditions. Vaginoscopy, in addition to being a non-invasive method, had the added advantage of predicting the fertilization period, thereby breeding advice could be more accurate as it helps in the visual inspection of vaginal mucosal folds. Pregnancy diagnosis was carried out in 20 animals at 20th, 35th and 50th day of gestation. Abdominal palpation at 20 days after breeding was non-confirmatory of pregnancy but at 35 days of gestation foetus could be appreciated as tense distinct uterine swellings. By ultrasound scanning at 20 days of gestation the image of embryonic vesicles appeared as spherical structures with anechoic consistency. No foetus or foetal membranes could be visualized at this stage. By day 25 to 27, echogenic foetal mass and heart beat became detectable. By day 28 to 33, head and body of the foetus were similar in size and revealed flickering heart beats. Anatomical features of the foetus became more obvious by about 34 to 39 days of gestation. Shape and size of the foetal head became distinguishable from the body at this stage. The percentage accuracy for transabdominal palpation at 20 days of gestation was found to be 20 per cent which improved to 75 per cent by about 35 days. The percentage accuracy at 50 days was 60 per cent. This study suggested that transabdominal palpation was not reliable in early and late gestation. For ultrasound scanning, the percentage accuracy at 20 days of gestation was found to be 15 per cent which improved to 90 per cent by 35 days. The percentage accuracy improved to 100 per cent by 50 days of gestation. Thus ultrasound scanning could be used as reliable tool for assessing the foetal viability. The level of serum alkaline phosphatase at 20th, 35th and 50th day of gestation was found to be 67.90 + 2.98, 91.85 + 2.10 and 139.65 + 6.84 U/L respectively. The level of haptoglobin at 20th day of gestation was 53.10 + 3.22 mg/dl where as the level elevated to 81.12 + 3.40 and 119.44 + 3.16 mg/dl by 35 days and 50 days of gestation respectively. The level of serum globulin at 20th, 35th and 50th day of gestation was 2.43 + 0.12, 3.05 + 0.11 and 3.74 + 0.15 g/dl respectively. Statistical analysis revealed significant difference between day 20 and day 50 (P<0.05). Thus the level of serum alkaline phosphatase, serum haptoglobin and serum globulin was found to be increasing as the pregnancy advanced and this could be used as indicators of healthy pregnancy. Total erythrocyte count (TEC) at 20, 35 and 50 days of gestation was 6.07 + 0.16, 5.58 + 0.15 and 5.12 + 0.16 million/cmm respectively. Haemoglobin concentration at day 20, 35th day and 50 days of gestation were found to be 11.86 + 0.28, 10.45 + 0.27 and 9.17 + 0.30 g/dl respectively. Packed cell volume values were 40.45 + 0.83, 37.30 + 0.87and 33.40+ 1.10 percent respectively at day 20, day 35 and 50 days of gestation. Erythrocyte sedimentation rate at day 20, day 35 and 50th day of gestation were found to be 10.31 + 0.73, 15.41 + 0.54 and 21.85 + 1.04 mm/hr respectively. Haemogram studies showed significant decrease in the total erythrocyte count, haemoglobin and packed cell volume at different gestational age (P<0.05). These changes were attributed by haemodilution and increased plasma volume. But erythrocyte sedimentation rate has shown an increase which could be attributed to the endometrial implantation by the embryo. The total leucocyte count at day 20, day 35 and day 50 of gestation was found to be 13844.90 + 539.90, 15449.00 + 569.86 and 17502.50 + 780.21 cells/cmm respectively. The neutrophil count at 20th, 35th and 50th day of gestation was 67.30 + 1.11, 70.30 + 4.95 and 75.35 + 1.27 per cent respectively. The lymphocyte count was found to be 27.80 + 0.87, 31.55 + 0.88 and 36.95 + 1.03 per cent at 20th, 35th and 50th days of gestation. Statistical analysis revealed significant variation between day 20 and day 50 in the neutrophil as well as lymphocyte count (P<0.05). Eosinophil count varied significantly (P<0.05) between day 20 and day 50 and the values were recorded as 1.60 + 0.11 and 3.30 + 0.13 per cent respectively. This was due to non-specific inflammatory response produced by the early embryo during endometrial implantation. The body weight of animals varied significantly (P<0.05) at different gestational age. Foetal viability was difficult to be monitored at 20 days of gestation. By ultra sound scanning, foetal heart beats could be observed in all pregnant animals from 25 days of gestation. The gestation length ranged between 58 to 69 days with an average of 63.30 + 3.76days. Litter size varied between three to eleven pups with a mean of 6.6 + 2.08 pups per bitch. The level of serum progesterone prior to treatment, post-treatment at 7th and 14th day were 1.11 + 0.14, 0.85 + 0.06 and 0.62 + 0.06 ng/ml respectively in cabergoline treated group while in bromocriptine treated group, it was 1.11 + 0.14, 0.5 + 0.01 and 0.5 + 0.01 ng/ml respectively. Statistical analysis showed significant difference between the serum progesterone values prior to treatment and the value obtained on 14th day after treatment (P<0.05). The concentration of prolactin in cabergoline treated group prior to treatment and at 7th and 14th day post-treatment was 6.17 + 2.05, 1.69 + 0.20 and 0.82 + 0.13 ng/ml respectively whereas in bromocriptine treated group the values were 6.02 + 1.17, 0.90 + 0.07 and 0.58 + 0.08 ng/ml respectively. Statistical analysis showed significant variation (P<0.05) in the serum prolactin level prior to treatment and at 7th and 14th day post-treatment. Antiprolactin drug cabergoline was found to be better than bromocriptine for treating pseudopregnancy at a dose rate of 5µg/kg BW orally for seven days with minimum side effects.